1977
DOI: 10.1139/e77-088
|View full text |Cite
|
Sign up to set email alerts
|

Middle and Upper Ordovician graptolites from the St. Lawrence Lowlands, Quebec, Canada

Abstract: Eleven species of Middle and Upper Ordovician graptolites are described and illustrated, a lectotype is selected for Orthograptus reudemanni (Gurley) and the occurrence of eighteen other species is recorded. The specimens were collected from sections along the Bécancour, Nicolet, Nicolet Sud-Ouest, and St. François Rivers of the St. Lawrence Lowlands, Quebec. The graptolite zonal scheme proposed by Riva for eastern North America is reviewed and adopted in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Zones of Nemagraptus gracilis and C. bicornis (Woods Hollow Shale), Marathon region, Texas (Berry, 1960). Zone of N. gracilis in the St. Lawrence lowlands, Quebec (Walters, 1977), in the Shelve district, British Isles (Strachan, 1986), and in Taimyr in the former USSR (Obut and Sobolevskaya, 1964). Also found in China (Wang and Jin, 1977).…”
Section: Figure 32gmentioning
confidence: 99%
“…Zones of Nemagraptus gracilis and C. bicornis (Woods Hollow Shale), Marathon region, Texas (Berry, 1960). Zone of N. gracilis in the St. Lawrence lowlands, Quebec (Walters, 1977), in the Shelve district, British Isles (Strachan, 1986), and in Taimyr in the former USSR (Obut and Sobolevskaya, 1964). Also found in China (Wang and Jin, 1977).…”
Section: Figure 32gmentioning
confidence: 99%
“…Synrhabdosomes occur in several morphotypes, but usually in small colonies such as simple dichograptids (Beckly & Maletz, 1991;Zalasiewicz 1984), various diplograptids and Saetograptus , as well as in Rhabdinopora flabelliforme. Complex central structures of floats have been recorded (Ruedemann 1947;Kozlowski 1949;Bulman 1970), but restudy of the original material has shown them to consist of nothing but abiogenic preservational artifacts (Rickards 1975;Walters 1977). Synrhabdosomes have been associated with both sexual (Zalasiewicz 1984) and asexual (Bulman 1970;Kozlowski 1949) reproduction of graptolites.…”
Section: The Graptolite As a Living Organismmentioning
confidence: 99%
“…This indicates that the black shales in the tectonosome units at Pointe Aubin are most likely blocks of Utica Shale from the underlying auto-chthonous platform. Walters (1979) identified graptolites within fault blocks ranging from the C. americanus to O. ruedemanni zones, meaning that they are, in fact, chronostratigraphic equivalents to the Upper Ordovician sequences of the foreland basin. New palynological data presented here also suggest that the tectonosome slices are imbricated foreland basin rocks that contain chitinozoan species reported in units of the Black River, Trenton, Utica, and Sainte-Rosalie groups of the Laurentian platform.…”
Section: Origin and Nature Of Component Rocks In Olistostrome And Tecmentioning
confidence: 99%
“…Siliciclastic rocks of the upper turbidite unit in the parautochthonous zone of the Québec City area were originally assigned to the Les Fonds Formation and the Breault and Chambly members of the Nicolet Formation, by Clark and Globensky (1973). Following detailed stratigraphic and sedimentologic work by Walters (1979), Walters et al (1982), and Beaulieu et al (1980), the parautochthonous flyschoid sediments were correlated to the Sainte-Perpétue and Sainte-Monique members of the redefined Rivière Nicolet Formation in the autochthonous zone ( Fig. 4).…”
Section: The Upper Turbidite Unitmentioning
confidence: 99%
See 1 more Smart Citation